Pelatihan Pemotretan Fashion Untuk Pemasaran Online Kalangan UMK Sebagai Upaya Bangkit Di Era Pandemi - Agus Pribadi; Hamdani Hamdani (LPPM Universitas Bumigora, 2022)
Covid-19 pandemic impact in Indonesia is felt by various groups, including micro and small business actors (UMK). The Covid-19 pandemic impact could reduce the operational and production capabilities of the fashion business in Mataram city, even to the point that it stops the business operation. Those condition is due to restrictions on community activities to prevent the spread of Covid-19. Online sales and digital marketing are solutions that comply with health protocols during the Covid-19 pandemic era. Digital marketing utilizes online media, e-commerce applications and social media. Digital marketing made the fashion product UMK actors for has additional skills in fashion product photography, in order to publish their products. Community service team in collaboration with the SpeedLight Management and Course organized photography training for the fashion product UMK actors. Training activities were carried out with methods/stages, initiation of training, socialization, training and practical assistance, as well as evaluation of the exercise results. 96,67% of training participants can be categorized able to make their own fashion product photos. Those achievement can make it easier for the fashion product UMK actors to make product publish in order for digital marketing.